Expression profiling of chemokines CCL8 and CXCL10 during peri-implantation period in Murrah buffaloes as a possible signature of embryonic implantation - KUMARI, RAJNI; DAYAL, S; SHARMA, I; KUMAR, S; CHANDRAN, P C; DEY, A; RAY, P K; KAMAL, R K; KUMAR, JYOTI; SARMA, KAMAL (The Indian Journal of Animal Sciences, 2021)
The present investigation was aimed to evaluate novel implication of chemokine genes CXCL10 (C-X-C motif chemokine 10) and CCL 8 (C-C motif chemokine 8) genes for use as ideal pregnancy biomarker in dairy buffaloes. We studied expression profile of both these chemokine genes in whole blood of Murrah buffaloes on day 12, 15, 18 and 21 post artificial insemination (AI) using SYBR green chemistry based quantitative real time reverse transcription PCR. Our investigations revealed a consistent increase in transcriptional abundance of CCL8 and CXCL10 genes during this period, although the difference in expression level was not significant between day 15 and 18 post AI for CXCL10 gene. We also studied the effect of parity on the expression profile of these two genes and found that expression level of both these genes is independent of parity status of the animal. Based on the results, it can be concluded that these chemokine genes can be used as early pregnancy biomarker on any day between days 12 to 21 post artificial insemination in buffaloes irrespective of their parity status.